PERICARDIAL MESOTHELIOMA WITH THROMBOVASCULAR COMPLICATIONS (CASE FROM PRACTICE) - N. Yu. Karpova; N. S. Chipigina; K. A. Rogov; A. M. Sdvizhkov; M. A. Rashid; J. I. Banova; E. M. Levin (Архивъ внутренней медицины, 2017)
Primary mesothelioma of the pericardium is a rare heart tumor with a difficult diagnosis, revealed in vivo in less than a quarter of cases. The disease occurs at any age, more common in men and variably exhibits a broad spectrum of non-specific symptoms of congestive heart failure, constrictive pericarditis, pericardial effusion or cardiac tamponade. Patients are usually observed with peripheral edema, ascites, dyspnea, cough, chest pain and atrial fibrillation. Such symptoms, in the absence of cancer alertness, are erroneously attributed by doctors to more common cardiovascular diseases. As a result, primary mesothelioma is detected in 75-90% of cases only at necropsy. The article describes a case of detection at autopsy of primary pericardial mesothelioma sarcomatous type with invasion into the myocardium in a patient of 74 years old. The patient also suffered from concomitant coronary artery disease with a long history of chronic heart failure and recurrent pulmonary embolism, associated with deep vein thrombosis at the final stage of the disease. An objective study revealed signs of chronic heart failure. The laboratory data included mild iron deficiency anemia, insignificant leukocytosis and leukocyturia, as well as signs of moderate chronic kidney disease. Instrumental results corresponded to long-term course of hypertension, signs of congestive heart failure in the presence of atrial fibrillation, atherosclerosis of lower limbs arteries in patient with abdominal obesity. Thus, there were no clinical signs of pericardial damage in a standard examination of the patient. The article describes the complexity of the disease diagnosis, variable clinical picture, as well as the diagnostic value of various instrumental methods from the perspective of evidence-based medicine. It is noted that clinical alertness is still the most important factor in the lifetime diagnosis of pericardial mesothelioma. Disease should be considered in patients with recurrent pericardial effusion, constrictive pericarditis, pericardial mass or thickening of pericardium leaflets. For reliable diagnosis of a tumor, modern imaging studies and histological examination are required.